Clinical and Metabolic Profile of Diabetes Mellitus in Children – One Year Cross-Sectional Study - V.D. Patil, S. M. Jali, M. B. Hiremath, Tanmaya Metgud* (Recent Research in Science and Technology, 2010)
Present study was aimed to study clinical presentations, metabolic profile, growth profile, type and prevalence of complications among the diabetic children. This Cross-sectional study was conducted among the 34 patients attending and admitted in our Hospital and District Hospital, Belgaum during the period of April – 04 to March -05. Patients with age less than 18 years and fasting blood sugar more than 126 mg/dl or random blood sugar more 200 mg/dl were included in the study. Patients with age more than 18 years were excluded from the study. All children attending our Hospital & M.R.C and District Hospital, Belgaum who are already diagnosed as Diabetes Mellitus were studied using a pre-designed and pre-tested proforma. Information was collected from the patient or attender or relative about sociodemographic profile, dietary intake and treatment history. In the present study 44.12% had onset of diabetes mellitus at 10 to 14 years age group with male to female ratio of 1.26:1. 20.51% had family history of diabetes and majority (41.18%) were from poor socio economic status. 73.33% were short statured in diabetic duration of more than one year and 31.57% in less than 1 year indicating growth deceleration. No children were obese and taller than the expected age group. 52.94% had poor glycemic control and was not influenced by duration of treatment as non compliance rates were high in the study. Majority presented with classical symptoms of polyuria, polydipsia, polyphagia and diabetic ketoacidosis as initial presentation. 50% had recurrent hospitalization in diabetic duration of more than 1 year. Negligible incidence of chronic complication was noted in the present study.